2014
DOI: 10.1051/0004-6361/201424133
|View full text |Cite
|
Sign up to set email alerts
|

Compensation of high-order quasi-static aberrations on SPHERE with the coronagraphic phase diversity (COFFEE)

Abstract: Context. The second-generation instrument SPHERE, dedicated to high-contrast imaging, will soon be in operation on the European Very Large Telescope. Such an instrument relies on an extreme adaptive optics system coupled with a coronagraph that suppresses most of the diffracted stellar light. However, the coronagraph performance is strongly limited by quasi-static aberrations that create long-lived speckles in the scientific image plane, which can easily be mistaken for planets. Aims. The wavefront analysis pe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 12 publications
2
27
0
Order By: Relevance
“…The K band is particularly interesting for this type of observations as adaptive optics systems are very efficient in this wavelength range, providing excellent correction of the atmospheric turbulence. Using a combination of coronagraphy and advanced processing techniques, the VLT/SPHERE instrument has demonstrated that sources with a contrast of 10 −4 or smaller can be detected down to an angular separation of ≈3λ/D = 0.2 with a high signal-to-noise ratio (Paul et al 2014). It has also been proposed recently that optimized correction techniques may significantly improve the accessible contrast (N'Diaye et al 2016), particularly in view of the E-ELT instrumentation.…”
Section: The Close Environment Of α Cen a And Bmentioning
confidence: 99%
“…The K band is particularly interesting for this type of observations as adaptive optics systems are very efficient in this wavelength range, providing excellent correction of the atmospheric turbulence. Using a combination of coronagraphy and advanced processing techniques, the VLT/SPHERE instrument has demonstrated that sources with a contrast of 10 −4 or smaller can be detected down to an angular separation of ≈3λ/D = 0.2 with a high signal-to-noise ratio (Paul et al 2014). It has also been proposed recently that optimized correction techniques may significantly improve the accessible contrast (N'Diaye et al 2016), particularly in view of the E-ELT instrumentation.…”
Section: The Close Environment Of α Cen a And Bmentioning
confidence: 99%
“…14 Though other variants, such as the coronagraphic focal plane wavefront estimation for exoplanet detection (COFFEE) 15 algorithm, have also been studied, stroke minimization and EFC have achieved the highest contrast of any controllers to date and are the primary control laws under consideration for the WFIRST-AFTA coronagraph system. In this section, we describe each, highlighting their differences and similarities.…”
Section: Monochromatic Model-based Control Algorithmsmentioning
confidence: 99%
“…(15) to be represented as the equality constraint ðI DH − C k Þ ¼ 0. Incorporating the equality constraint for the central wavelength into the minimization on stroke via a Lagrange multiplier, μ k , yields a quadratic cost function given by E Q -T A R G E T ; t e m p : i n t r a l i n k -; e 0 1 6 ; 3 2 6 ; 2 9 9…”
Section: Stroke Minimization-lagrange Multipliersmentioning
confidence: 99%
See 1 more Smart Citation
“…ZELDA; N'Diaye et al 2013), coronagraphic phase diversity (e.g. COFFEE; Paul et al 2013Paul et al , 2014, energy minimization or electric field conjugation (Bordé & Traub 2006;Give'On et al 2007), or any combination of these methods.…”
Section: Experimental Results and Comparison To Simulationsmentioning
confidence: 99%